Monozygotic multiple pregnancies after transfer of single in vitro produced equine embryos. (4th September 2019) - Dijkstra, A.; Cuervo‐Arango, J.; Stout, T. A. E.; Claes, A.
Summary: Background: Monozygotic multiple pregnancy is rare in horses, but may be more common after transfer of an in vitro produced (IVP) embryo. Objectives: To determine the occurrence, incidence, characteristics and outcome of monozygotic siblings arising from in vivo and IVP equine embryos. Study design: Retrospective case series. Methods: A total of 496 fresh in vivo and 410 frozen‐thawed IVP blastocysts, produced by intracytoplasmic sperm injection (ICSI) of in vitro matured oocytes from Warmblood mares, were transferred into recipient mares. The likelihoods of pregnancy and multiple pregnancy were calculated, and the clinical features and outcome of any multiple pregnancy were recorded. Results: The likelihood of pregnancy after transfer of a single IVP or in vivo embryo was 62% (254/410) and 83% (413/496) respectively. The incidence of multiple pregnancy was 1.6% (4/254) and 0% (0/413) for IVP and in vivo blastocysts, respectively. More specifically, three IVP blastocysts yielded twin embryo propers/fetuses, and one IVP conceptus developed three distinct embryonic bodies. Interestingly, only one embryonic vesicle was detected at all ultrasonographic examinations prior to embryo proper development. Multiple embryonic bodies only became apparent at later scans to check for an embryo proper and heartbeat, or when the recipient mare aborted. Two twin pregnancies aborted spontaneously at 3 and 9 months, respectively, while the heartbeat was lost from all three embryos in the triplet pregnancy before day 35 of gestation. Twin reduction by per rectum compression of one fetal thorax was attempted at day 50 of gestation in the fourth case; however, both fetuses were lost. Main limitations: Small number of cases. Conclusions: In vitro embryo production resulted in a higher incidence of multiple monozygotic pregnancy, which could only be diagnosed after development of the embryo proper and is likely to result in pregnancy loss later in gestation if left untreated.